Exploitation of trypanotolerance traits in field conditions - D'Ieteren, G.D.M. (European Union, 2001)
Further to understand the mechanisms underlying trypanotolerance, the exploitation of resistance traits relies on the characterisation of these traits in the field and their practical measurement. The successful use of any criteria for identification of trypanotolerant breeds of cattle and/or superior animals within these breeds depends on the practicality of their measurement, on the strength of the linkage of the criteria with the economically important production traits such as viability, reproductive performance and growth, and on the associated genetic parameters. This paper discusses the relation between measurements of trypanotolerance livestock performance; genetics of trypanotolerance measurements; and future exploitation.